The Choral Works of Jennifer Higdon : Choral Kaleidoscope - Skoog, William (Cambridge Scholars Publisher, 2021)
Jennifer Higdon is an esteemed American composer known internationally, and the recipient of many awards in various musical genres. Though best known for her instrumental works and operas, she is a prolific writer of choral music that is fascinating, varied in style, profound, and meaningful, and speaks directly to a contemporary audience through the carefully selected texts. This book explores a number of Higdon's choral works, both extended and short works, citing the extensive relationship of the music to the texts, which are set a cappella, with full orchestra or with chamber instruments. A.